Circulation in the Seaflower Reserve and Its Potential Impact on Biological Connectivity - Lopera, Luisa; Cardona, Yuley; Zapata-Ramírez, Paula A. (Frontiers in Marine Science, 2020)
The influence of ocean currents on marine population connectivity is critical to territory planning, and such phenomena should be considered in the design and implementation of marine protected areas (MPAs), marine spatial planning strategies, and restoration plans, among other developments. Knowledge of the influence of currents is also vital in understanding the relationship between oceanographic drivers and ecosystem configurations. However, despite their importance, ocean currents and their role in coral connectivity remain poorly constrained in the Seaflower Marine Reserve, an area that hosts the most productive open-ocean coral reef system in the Caribbean and that was declared a biosphere reserve in 2000. We herein characterize the larva transport patterns associated with surface currents that control connectivity in the reserve. To achieve this aim, we simulated the advection of buoyant coral larvae of Acropora palmata during nine spawning events. Larval dispersal patterns were obtained through offline coupling of a high-spatiotemporal resolution hydrodynamic field and a biophysical Lagrangian model for particle dispersion. Ocean current fields were generated using a Regional Ocean Modeling System (ROMS) that was appropriately configured for the region. Larval dispersion was simulated using an Individual-Based Model (Ichthyop). Our results show that there are heterogeneous connectivity patterns during the spawning events at seasonal and inter-annual scales. This seems to be associated with high spatiotemporal dynamic variability in the region, such as the Caribbean Current bifurcation close to the Nicaraguan Rise, the intrusion-formation of mesoscale and sub-mesoscale eddies, and the semi-permanent presence of the Panama-Colombia Gyre. We also found that Serranilla, Providencia, Quitasueño, and Serrana act as the most important sinks. In contrast, the northernmost reefs, Serranilla, B. Alicia, and B. Nuevo, seem to be the most important sources of larvae, highlighting that these areas need to be incorporated into the current MPA zonification and that this could lead to the improvement of MPA effectiveness. Our findings also suggest the need to implement MPA networks between Jamaica and Colombia to allow biological populations to become resilient to environmental changes and less prone to local extinctions.